Escherichia coli producing colibactin triggers premature and transmissible senescence in mammalian cells. - Thomas Secher; Ascel Samba-Louaka; Eric Oswald; Jean-Philippe Nougayrède (PLoS ONE, 2013)
Cellular senescence is an irreversible state of proliferation arrest evoked by a myriad of stresses including oncogene activation, telomere shortening/dysfunction and genotoxic insults. It has been associated with tumor activation, immune suppression and aging, owing to the secretion of proinflammatory mediators. The bacterial genotoxin colibactin, encoded by the pks genomic island is frequently harboured by Escherichia coli strains of the B2 phylogenetic group. Mammalian cells exposed to live pks+ bacteria exhibit DNA-double strand breaks (DSB) and undergo cell-cycle arrest and death. Here we show that cells that survive the acute bacterial infection with pks+ E. coli display hallmarks of cellular senescence: chronic DSB, prolonged cell-cycle arrest, enhanced senescence-associated β-galactosidase (SA-β-Gal) activity, expansion of promyelocytic leukemia nuclear foci and senescence-associated heterochromatin foci. This was accompanied by reactive oxygen species production and pro-inflammatory cytokines, chemokines and proteases secretion. These mediators were able to trigger DSB and enhanced SA-β-Gal activity in bystander recipient cells treated with conditioned medium from senescent cells. Furthermore, these senescent cells promoted the growth of human tumor cells. In conclusion, the present data demonstrated that the E. coli genotoxin colibactin induces cellular senescence and subsequently propel bystander genotoxic and oncogenic effects.